The Market for borrowing securities in Brazil - Mota, Lira Rocha da (2013)
We report the results of an exploratory data analysis of the Brazilian securities lending market. The analysis is performed over the full historical data set of each individual loan offer and loan contract negotiated between January 2007 and August 2013. We give a quantitative description of volume and loan fee trends and fee dependence on asset characteristics. We also unveil new stylized facts specific to the Brazilian market on market access asymmetries between different types of investors. The emerging picture is that the Brazilian securities lending market is a complex environment with specific frictions and strong asymmetries among players. In particular, we describe a tax arbitrage operation performed by domestic mutual funds which generates a significant distortion in the data. In one such event, we estimate additional aggregate profits of 24.25 million Reais (around 10 million Dollars).